Targeting Ferroptosis Attenuates Inflammation, Fibrosis, and Mast Cell Activation in Chronic Prostatitis - Dongxu Lin; Mengyang Zhang; Changcheng Luo; Pengyu Wei; Kai Cui; Zhong Chen (Journal of Immunology Research)
Purpose. Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common urological disorder. Although ferroptosis is closely associated with inflammation, oxidative stress, and neuropathic pain, its role in CP/CPPS has not yet been elucidated. Therefore, we sought to explore the role and mechanism of ferroptosis in the prostatitis development. Methods. The experimental autoimmune prostatitis (EAP) was established through intradermal immunization of prostate extract. Iron chelator deferoxamine (DFO) and free radical scavenger edaravone (EDA) were applied to evaluate the effects of ferroptosis inhibition on oxidative stress, ferroptosis, inflammation, fibrosis, and mast cell activation in the context of CP/CPPS. Results. Increased generation of lipid peroxidation products (ROS and MDA) and decreased activities of antioxidant enzymes (SOD and CAT) suggested an aberrant oxidative stress status in EAP model. Elevated iron concentration was observed in the EAP model. Meanwhile, we discovered significant biological performances associated with ferroptosis in CP/CPPS, including the downregulation of the system Xc-/GPX4 axis and the upregulation of the ACSL4/LPCAT3 axis. EAP rats performed serious leukocyte infiltration, advanced inflammatory grade, and abnormal expression of inflammatory mediators. Abundant collagen deposition, enhanced RhoA, ROCK1, and α-SMA protein levels indicated that EAP rats were prone to suffer from stromal fibrosis compared with control group. An elevated number of degranulated mast cells and corresponding marker TPSB2 represented that mast cell-sensitized pain was amplified in the EAP model. Furthermore, reduction of NRF2/HO-1 indicated a vulnerability of EAP towards ferroptosis response. However, application of DFO and EDA had partially reversed the adverse influences mentioned above. Conclusion. We first demonstrated that ferroptosis might be a crucial factor of chronic prostatitis progression. Inhibition of ferroptosis using DFO and EDA represented a promising approach for treating prostatitis by ameliorating inflammation, fibrosis, and mast cell activation.